Learning from Loss: The Story of a Student Rebuilding His Motivation to Study After His Father Passed Away - Anisa Rahmawati; Fajar Kawuryan (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The death of a father during a student’s university years is a deeply disruptive emotional experience that can undermine personal stability and significantly affect learning motivation. At this developmental stage, students are expected to manage independence and academic responsibilities, making the loss of a paternal figure likely to trigger reduced enthusiasm, concentration difficulties, and shifts in how they interpret the learning process. This study aims to explore the dynamics of learning motivation among students who experienced paternal loss by employing a qualitative phenomenological approach. Three undergraduate students aged 19–23 who lost their fathers during their studies participated in the research. Data were collected through in-depth interviews and observations and analyzed using thematic coding. The findings indicate meaningful changes across four motivational aspects: drive, commitment, initiative, and optimism. Initially, all participants experienced a decline in motivation characterized by sadness, decreased focus, and weakened academic goals. Over time, however, their motivation gradually rebuilt through personal reflection, family support, social responsibility, and the development of new meaning in their educational pursuits. These results imply the need for higher education institutions to provide more responsive psychological and academic support to bereaved students in order to facilitate adaptive recovery and sustain their academic engagement.